Cow Dung Biostabilized Earth Mortars: Reusability and Influence of Cow Dung Processing and Cow Diet - Raphael N. Pachamama; Paulina Faria; Marco A. P. Rezende; Patrícia M. Moraes (Buildings)
Historically, cow dung has been widely used as a biostabilizer in earth building, although the scientific research on this subject is still limited. The available research provides evidence of the positive effects of this bioaddition on earthen blocks and plasters, as it improves their physical and mechanical properties and durability in water contact. The present research does not aim to characterize biostabilized earthen mortars or to explain the interaction mechanisms between the earth and cow dung components, because this topic has already been investigated. Instead, it aims to investigate strategies to optimize the collection and processing of cow dung so as to optimize their effects when used in earth-plastering mortars, as well as considering the effects of using them fresh whole, dry whole, and dry ground (as a powder); the effects of two different volumetric proportions of cow dung addition, 20% and 40% (of the earth + added sand); the effects of 72 h (fermentation–humid curing) before molding the biostabilized mortar; the influence of the cow diet; and the potential of reusing cow dung stabilized mortars. The results show that as the freshness of the cow dung increases, the mortar’s durability increases under water immersion, as well as the mechanical and adhesive strength. Collecting cow dung fresh and drying (composting) it in a plastic container is more efficient than collecting cow dung that is already dry on the pasture. The cow diet and the use of dry (composted) cow dung, whole or ground into a powder, does not result in a significant difference. A 72 h period of humid curing fermentation increases the adhesive strength and durability under water. The proportion of 40% promotes better durability under water, but 20% offers greater mechanical and adhesive strength. Finally, cow dung addition does not reduce the reusability of the earth mortar. The new mortar obtained by remixing the mortar with water presents increased properties in comparison to the original reference mortar with no cow dung addition. Therefore, the contributions of this research are innovative and important, offering technical support in the area of biostabilized earth-plastering mortars. Furthermore, it is emphasized that cow dung addition can be optimized as an efficient traditional solution to increase the mechanical resistance, but especially to increase the durability of earth mortars when in contact with water. This effect is particularly important for communities lacking financial resources, but also reveals the possibility of using eco-efficient waste instead of binders obtained at high firing temperatures.